2011
DOI: 10.1029/2010jf001948
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal speedup of a Greenland marine-terminating outlet glacier forced by surface melt–induced changes in subglacial hydrology

Abstract: [1] We present subdaily ice flow measurements at four GPS sites between 36 and 72 km from the margin of a marine-terminating Greenland outlet glacier spanning the 2009 melt season. Our data show that >35 km from the margin, seasonal and shorter-time scale ice flow variations are controlled by surface melt-induced changes in subglacial hydrology. Following the onset of melting at each site, ice motion increased above background for up to 2 months with resultant up-glacier migration of both the onset and peak of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
152
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 141 publications
(162 citation statements)
references
References 68 publications
9
152
1
Order By: Relevance
“…Sole et al [110] found transient seasonal acceleration and subsequent deceleration of ice flow in response to surface meltwater inputs to the bed at sites > 35 km inland from a tidewater glacier terminus in south-west Greenland, indicating parallels between land-and marine-terminating subglacial hydrology. For a number of stable tidewater glaciers in west Greenland, Howat et al [111] reached similar conclusions based on remote sensing of ice velocity 4-6 km from their termini.…”
Section: The Influence Of Hydrology On Marine Terminating ('Tidewatermentioning
confidence: 99%
“…Sole et al [110] found transient seasonal acceleration and subsequent deceleration of ice flow in response to surface meltwater inputs to the bed at sites > 35 km inland from a tidewater glacier terminus in south-west Greenland, indicating parallels between land-and marine-terminating subglacial hydrology. For a number of stable tidewater glaciers in west Greenland, Howat et al [111] reached similar conclusions based on remote sensing of ice velocity 4-6 km from their termini.…”
Section: The Influence Of Hydrology On Marine Terminating ('Tidewatermentioning
confidence: 99%
“…3). Additionally, the ice-margin advance flushed out pressurized subglacial water from the glacier base, a phenomenon that occurs in modern settings (36) and that can be inferred from modeling (41). Through the reduction of subglacial water availability, both phenomena diminish subglacial buoyancy, leading to increased basal friction.…”
Section: Regional Climate Forcingsmentioning
confidence: 99%
“…This triggered ice-margin thinning and acceleration (Fig. 3) and the attendant increased calving rate (34)(35)(36)(37) (Fig. 3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…V ariations in the Greenland Ice Sheet (GrIS) flow have been observed on timescales varying from hours to years [1][2][3][4][5][6][7] . In particular, the sudden delivery of surface meltwater to the bed during supraglacial lake (SGL) drainage events drive pronounced although short-lived, accelerations in flow 1,2 .…”
mentioning
confidence: 99%